Ecological and nutritional implications of the mandibular structure in the Antarctic calanoid copepod Metridia gerlachei Giesbrecht, 1902: an ultrastructural study - ROMANO, PAOLA; MARIOTTINI, GIAN LUIGI; CARLI, ANNA MARIA; M. Feletti (Springer-Vetlag, 1999)
In Antarctic sea waters the composition and structure of living communities and the morphology of species are strongly affected by low temperatures; furthermore, the environmental conditions and the adaptive strategies promoted evolution efforts and development of endemisms. Scanning electron microscopy can greatly contribute to the knowledge of structures differentiating high-latitude organisms from similar species inhabiting other marine environments. This work reports some ultrastructural details of the mandibles of Metridia gerlachei (Copepoda, Calanoida) adult females sampled during the Italian Antarctic Campaign 1987/1988 in order to verify the known descriptions and to emphasize some characters related to feeding habits. The observation of mandibles by light and scanning electron microscopy allowed us to verify that the morphological characters are connected with behaviour, food uptake and diet composition, and confirmed the omnivory of the species. The ultrastructural observations reported here have improved our knowledge about the role of Metridia gerlachei in the Antarctic food-web.